Conducta obstétrica en multigesta nulípara de 25 años de edad embarazada de 15.5 semanas con infección de vías urinarias - Olvera Becilla, María Fernanda (2021)
TOPIC: Urinary tract infections in pregnancy is the presence of pathogenic microorganisms in the urine, either due to infection in the bladder or kidney, among the most common in 80% is Escherichia coli, urinary tract infections have a incidence of 5% to 10% in pregnancy, for this reason it is encouraged to carry out the report of the case of a 25-year-old patient with a 15.5-week pregnancy at the Hospital Sagrado Corazón de Jesús. OBJECTIVE: It is proposed to analyze the clinical case of said patient with urinary tract infection that was diagnosed by the clinical picture and urinalysis, presents risk factors that caused the clinical picture. METHODOLOGY: The study is observational, clinical and descriptive. The patient is hospitalized for at least 48 to 72 hours until there is a thermal drop, oral treatment is continued, in case of persistent fever, measures such as volume control, antipyretics, temperature control every 12 hours are used, control of diuresis every 24 hours, control of uterine dynamics every 12 hours, post obstetric evaluation, medical discharge with oral treatment for 14 consecutive days, with urine culture control 1 to 2 weeks after the medical prescription was completed. RESULT AND CONCLUSION: Pregnant woman with urinary tract infection that was managed with Antibiotic therapy and complementary tests, which progressed favorably and medical discharge was prescribed. The patient's management was expectant according to the MSP's Clinical Practice Guideline. Patient with recurrent urinary tract infections and domestic violence that caused vulnerability to said pathology.